2017
DOI: 10.1111/jgs.14812
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Consumption and Incident Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study

Abstract: This cohort study suggests that frequent mushroom consumption is significantly associated with a lower risk of incident dementia, even after adjustment for possible confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 48 publications
1
46
2
Order By: Relevance
“…Dietary ET does cross the blood–brain barrier, since it can be measured in human cerebrospinal fluid and postmortem brain samples (our unpublished data; also see ) and readily enters the brain when administered to mice . A Japanese study has found a correlation between increased intake of mushrooms (one of the most important dietary sources of ET ; Table ) and lower incidence of dementia. However, mushrooms are known to contain a wide range of possibly bioactive compounds that could account for this observation.…”
Section: Ergothioneine As a Potential Treatment For Diseasesmentioning
confidence: 82%
See 1 more Smart Citation
“…Dietary ET does cross the blood–brain barrier, since it can be measured in human cerebrospinal fluid and postmortem brain samples (our unpublished data; also see ) and readily enters the brain when administered to mice . A Japanese study has found a correlation between increased intake of mushrooms (one of the most important dietary sources of ET ; Table ) and lower incidence of dementia. However, mushrooms are known to contain a wide range of possibly bioactive compounds that could account for this observation.…”
Section: Ergothioneine As a Potential Treatment For Diseasesmentioning
confidence: 82%
“…readily enters the brain when administered to mice [33]. A Japanese study [74] has found a correlation between increased intake of mushrooms (one of the most important dietary sources of ET [27-29]; Table 1) and lower incidence of dementia. However, mushrooms are known to contain a wide range of possibly bioactive compounds that could account for this observation.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…individuals who had impairment with mild cognitive dysfunction, but who had no dementia-related symptoms or behavioral disturbance and were capable of living independently are ranked as I; and individuals ranked as greater than or equal to II or M (rank M means that the individual has severe dementia-related symptoms and requires medical services) are regarded as having incident dementia. 16,17 In previous studies, the dementia scale of LTCI certification has been shown to be well-correlated with the Hasegawa's Dementia Scale (HDS-R) (Spearman's rank correlation coefficient ρ = −0.732)…”
Section: Key Pointsmentioning
confidence: 98%
“…16,17 In previous studies, the dementia scale of LTCI certification has been shown to be well-correlated with the Hasegawa's Dementia Scale (HDS-R) (Spearman's rank correlation coefficient ρ = −0.732) 16,17 In previous studies, the dementia scale of LTCI certification has been shown to be well-correlated with the Hasegawa's Dementia Scale (HDS-R) (Spearman's rank correlation coefficient ρ = −0.732)…”
Section: Key Pointsmentioning
confidence: 99%
“…These criteria remained unchanged throughout the follow‐up period. In previous studies, the Dementia Scale of LTCI certification has been shown to correlate well with Hasegawa's Dementia Scale and the Mini‐Mental State Examination Scale, and has been applied as a measurement of incident dementia in older adults in Japan . We obtained LTCI information from the Okayama City Public Health Center under privacy protection.…”
Section: Methodsmentioning
confidence: 99%